VALUE CHAIAN OF WHEAT CROP IN BAGHDAD PROVINCE/IRAQ AN APPLIED STUDY FOR YEAR 2017 - AL- FALLUJI, S.J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Wheat is one of the most important strategic crops that have an important role in people's life and food security. Therefore, the research depends on the methodology value chain analyses to discuss and follow the most important determinants and problems facing wheat value chains in Iraq, as well as analyzing the costs and revenues for a different series of the chains, and then calculate the profits and value added in each of its chain .The results showed that the achieved profits by the producers of the wheat crop was 384258 dinar / dunum, while the value by weight was 371263.9 dinar / ton, The added value of the wheat producers and the marketing chain when the grain is delivered by  (local wholesalers) was 212000.8 ID / ton, while the added value for crop producers and the marketing chain was 347000.8 dinar / ton when the crop is delivered by government Grain Stores , this represents a significant difference between the values by 135000 dinars that representing 39% of the total added value, while the added value of local traders was 88000 dinar / ton for first class grain and 48000 dinar / ton to second class grain . Also research identified many problems and obstacles that face the value chain of wheat , which have negative and reflective effects on the wheat production cycle and the added value, which were cleared by the questionnaire. These include: high costs of automation and fields preparation for cultivation , which is equal 52% of the total variable costs. As well as the high costs of production requirements included: fertilizers, seeds, fuel, oil , electricity, and control materials. Etc.), which was 22%, 8.1%, 7.6% and 5.4%, respectively, and inadequate quantities that received from the state, in addition the marketing which suffers from many problems and obstacles and boring routine and inefficiency of its operating systems which has lost confidence in the direct dealings between farmers and management of state stores, Finally the research included several conclusions and recommendations to the relevant authorities for solving the problems and obstacles in the value chains of the wheat crop in Iraq to increase the competitiveness of this crop in the local and regional market.